2010
DOI: 10.1063/1.3296121
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure behavior of β-Ga2O3 nanocrystals

Abstract: Freestanding nanocrystalline ␤-Ga 2 O 3 particles with an average grain size of 14 nm prepared by chemical method was investigated by angle-dispersive synchrotron x-ray diffraction in diamond-anvil cell up to 64.9 GPa at ambient temperature. The evolution of x-ray diffraction patterns indicated that nanocrystalline monoclinic ␤-Ga 2 O 3 underwent a phase transition to rhombohedral ␣-Ga 2 O 3 . It was found that ␤-to ␣-Ga 2 O 3 transition began at about 13.6-16.4 GPa, and extended up to 39.2 GPa. At the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…It has been revealed that the transformation between α and β phases of Ga 2 O 3 is very sluggish . It is implied that the composition evolution with time at a given temperature may give hints about the process of the phase transformation.…”
Section: Resultsmentioning
confidence: 99%
“…It has been revealed that the transformation between α and β phases of Ga 2 O 3 is very sluggish . It is implied that the composition evolution with time at a given temperature may give hints about the process of the phase transformation.…”
Section: Resultsmentioning
confidence: 99%
“…HP studies in group-13-SOs have been conducted on the five compounds. Al 2 O 3 , also known as alumina, is by far the most studied compound [85][86][87][88][89][90][91][92][93][94][95][96][97][98][99], followed by In 2 O 3 [100][101][102][103][104][105][106][107][108][109], Ga 2 O 3 [107,[110][111][112][113][114], and B 2 O 3 [115][116][117][118][119][120][121]. Finally, Tl 2 O 3 has been the least studied compound [122].…”
Section: Group-13 Sesquioxidesmentioning
confidence: 99%
“…Additionally, the anisotropy of the observed unit cell expansion is inconsistent with the known elastic properties of β-Ga 2 O 3 . High pressure experiments [39,40] show that, under hydrostatic stress conditions, this material is softest in the [100] and hardest in the [001]. Thus, the formation of over-dense amorphous tracks in a polycrystalline pellet of random crystallite orientation would be expected to produce unit cell expansion that is greatest in a and least in c. In contrast, the data presented in Fig.…”
Section: Similarly Direct Scanning Transmission Electron Microscopy mentioning
confidence: 99%